ANALISIS INTEGRASI PROGRAM ADMINISTRASI KEBIJAKAN KESEHATAN, EPIDEMIOLOGI, DAN KESEHATAN LINGKUNGAN PADA DINAS KESEHATAN ACEH SELATAN - Reza Kurnia; Alda Syaqhia Nella; Mika Sari; Lucy Irwya Bariska; Nadiyatul Maghfirah (Public Health Journal, 2026)
This internship report aims to analyze the integration of Health Administration Policy, Epidemiology, and Environmental Health programs at the Aceh Selatan District Health Office. The implementation of integrated health programs is essential because public health problems have complex causative factors that cannot be resolved through a single program alone. This internship was conducted from May 25 to June 22, 2026, at the Aceh Selatan District Health Office. The methods used include direct observation, participation in various administrative and technical activities, and document review. The results show that the integration of the three programs has been partially implemented, but still faces various challenges such as coordination between programs, inter-sectoral communication, and the integration of health information systems. Efforts to strengthen integration can be made through improving cross-program coordination, joint planning, utilization of health information for decision-making, and strengthening the health management system. This internship provides valuable experience for students in understanding the dynamics of health services at the district level and the importance of program integration in achieving health development goals.